Conservation Practice and the Future of Doctrinal Texts - Nigel Walter (Ochrona Dziedzictwa Kulturowego)
2021 marks the 90th anniversary of the adoption of the Athens Charter. This, the first international conservation charter, now forms part of the rapidly expanding collection of ‘doctrinal texts’ which undergirds modern conservation. Whatever its strengths and weaknesses, this collection provides a marker of collective identity and is crucial to the self-definition of our discipline.